Linking HYSYS with CFD: Study of Centrifugal Compressor Operations - Mohd Sahak, Muhammad Zakwan (Universiti Teknologi Petronas, 2011)
The flow through a centrifugal compressor which consists of 20 impeller blades and 19 diffuser blades is simulated using NUMECA FINEffUibo. The geometry of the compressor was done by using AutoBiade. Test variations were conducted for meshing and discretization for selecting the best alternative for the test. The result is validated using a published journal. The values and parameters of the simulation result were then transferred to Aspen HYSYS to see the agreement of the values. An error of0.19% is obtained from the static temperature at outlet.